Fingerprint Authentication by Wavelet-based Digital Watermarking - Rajlaxmi Chouhan; Agya Mishra; Pritee Khanna (Institute of Advanced Engineering and Science, 2012)
In this manuscript, a wavelet-based blind watermarking scheme has been proposed as a means to provide protection against false matching of a possibly tampered fingerprint by embedding a binary name label of the fingerprint owner in the fingerprint itself. Embedding watermarks in the detail regions allow us to increase the robustness of our watermark, at little to no additional impact on image quality. It has been experimentally shown that when a binary watermark is embedded into detail coefficients of an indexed fingerprint image in a spread spectrum fashion, the perceptual invisibility and robustness have anticlinal response to change in amplification factor “K” and smaller watermarks have better transparency than the larger ones. The DWT-based technique has been found to give better robustness against noises, geometrical distortions, filtering and JPEG compression attack than other frequency domain watermarking techniques.DOI:http://dx.doi.org/10.11591/ijece.v2i4.505